2014
DOI: 10.3748/wjg.v20.i24.7926
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopicvsopen extended right hemicolectomy for colon cancer

Abstract: LERH with D3 lymphadenectomy for colon cancer is a technically feasible and safe procedure, yielding comparable short-term oncologic outcomes to those of open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 26 publications
2
53
1
Order By: Relevance
“…No heterogeneity was found between the studies for overall survival, which ranged from 67% to 91%, and for disease‐free survival ( I 2 = 0). Meta‐analysis showed no significant difference between the two groups [HR = 1.20 (95% CI: 0.94–1.53); P = 0.14) in terms of overall survival. Four of the selected studies reported disease‐free survival.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No heterogeneity was found between the studies for overall survival, which ranged from 67% to 91%, and for disease‐free survival ( I 2 = 0). Meta‐analysis showed no significant difference between the two groups [HR = 1.20 (95% CI: 0.94–1.53); P = 0.14) in terms of overall survival. Four of the selected studies reported disease‐free survival.…”
Section: Resultsmentioning
confidence: 99%
“…Meta‐analysis showed no significant difference between the two groups [HR = 1.20 (95% CI: 0.94–1.53); P = 0.14) in terms of overall survival. Four of the selected studies reported disease‐free survival. There was no statistically significant difference between the two groups [HR = 1.17 (95% CI: 0.95–1.44); P = 0.14] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations